Examining the role of ambidextrous green innovation and green competitive advantage in stimulating sustainable performance: The moderating role of green absorptive capacity - Baquero, Asier (SAGE Open, 2024)
Hotels’ sustainable performance has become a key issue in tourism. We examine the role of ambidextrous green innovation (GI) and its relationship with sustainable performance, considering the mediating effect of green competitive advantage and moderating effect of green absorptive capacity. Data were collected through a questionnaire survey of Spanish hotels. We utilize variance-based partial least squares structural-equation modelling (PLS-SEM) for analysis. We find that ambidextrous GI significantly impacts the economic, social, and environmental aspects of sustainable performance. Additionally, green competitive advantage mediates the relationship between ambidextrous GI and sustainable performance, while the moderating effect of green absorptive capacity strengthens the impact of ambidextrous GI on environmental performance. However, green absorptive capacity does not significantly moderate the associations between ambidextrous GI and social and environmental performance. To enhance hotels’ sustainability, further investigation into the interaction between tangible and intangible resources and ambidextrous GI is indicated. This study offers valuable insights for hotel management to enhance sustainable performance.
Keywords: ambidextrous green innovation; sustainable performance; green competitive advantage; green absorptive capacity; hospitality business; JCR